The mycoparasitic yeast Saccharomycopsis schoenii predates and kills multi-drug resistant Candida auris. Issue 1 (December 2018) - Junker, Klara; Bravo Ruiz, Gustavo; Lorenz, Alexander; Walker, Louise; Gow, Neil; Wendland, Jürgen
Abstract Candida auris has recently emerged as a multi-drug resistant fungal pathogen that poses a serious global health threat, especially for patients in hospital intensive care units (ICUs).C. auris can colonize human skin and can spread by physical contact or contaminated surfaces and equipment. Here, we show that the mycoparasitic yeastSaccharomycopsis schoenii efficiently kills both sensitive and multi-drug resistant isolates ofC. auris belonging to the same clade, as well as clinical isolates of other pathogenic species of theCandida genus suggesting novel approaches for biocontrol.